Slow magnetic relaxation of a mononuclear dysprosium complex derived from 4, 4, 4-trifluoro-1-(2-naphthyl)-1, 3-butanedione and 1, 10-phenanthroline. (5th January 2023) - Liu, Shan-Shan; Guo, Qi-Ming; Liu, Bin; Jin, Teng-Hui; Zhang, Zi-Hao; Lin, Shijing; Meng, Yin-Shan
Abstract : A mononuclear dysprosium complex with a triangular dodecahedron geometry behaves as a single-molecule magnet with the effective barrier U eff = 193 K. Abstract : Two mononuclear complexes, [(tfnb)3 Ln(phen)] (Ln = Tb or Dy, tfnb = 4, 4, 4-trifluoro-1-(2-naphthyl)-1, 3-butanedione, phen = 1, 10-phenanthroline), were isolated and structurally determined using single crystal X-ray diffraction techniques. The crystallographic data reveal that the two complexes are isostructural and adopt a trigonal dodecahedral geometry. The dysprosium complex exhibits a slow relaxation of the magnetization in the absence of a dc field. A combination of QTM, Raman and Orbach processes was considered in energy barrier fitting, giving the effective barrier U eff = 193 K. The magnetic easy axis calculated using an electrostatic model follows the direction of the two tfnb − ligands in the trans position.